Unraveling the presence of multi-class toxins from Trichodesmium bloom in the Gulf of Mannar region of the Bay of Bengal. (1st September 2017) - Shunmugam, Sumathy; Gayathri, Manickam; Prasannabalaji, Nainangu; Thajuddin, Nooruddin; Muralitharan, Gangatharan
Abstract: Trichodesmium is an enigmatic bloom forming, non-heterocystous cyanobacterium reported most frequently in the coastal waters of India. However, the toxigenic potential of this globally significant N2 fixing cyanobacterium has not been characterized. In this study, we report for the first time the presence of potent multi-class neurotoxins such as Anatoxin-a, Saxitoxins, Gonyautoxin and hepatotoxins like MC-LR, MC-YA from a bloom material of Trichodesmium sp. MBDU 524 collected at the Gulf of Mannar region. Toxins were determined using liquid chromatography-electrospray ionization mass spectrometry (LC-ESI-MS) analysis of HPLC purified aqueous and solvent fractions. Molecular phylogenetic analysis through 16S rRNA gene sequencing showed the close relationship with Trichodesmium erythraeum clade. The toxigenic potential was validated through brine shrimp toxicity assay and showed 100% mortality after 48 h of incubation. The results suggest the potential toxigenic and environmental impacts of Trichodesmium bloom sample from the Gulf of Mannar region. Highlights: Trichodesmium is a key primary producer that contributes to global nitrogen balance. This is the first report showing toxins from Trichodesmium bloom from Indian waters. The extracts of Trichodesmium sp. MBDU 524 showed 100% toxicity against A. salina .